Effect of endophytic Fusarium oxysporum on host preference of Radopholus similis to tissue culture banana plants - Athman, S.; Dubois, T.; Coyne, D.; Gold, C.; Labuschagne, N.; Viljoen, Altus (2006)
The burrowing nematode Radopholus similis is one of the major constraints to banana (Musa spp.) production worldwide. Resource-poor farmers can potentially manage R. similis by using naturally occurring banana endophytes, such as nonpathogenic Fusarium oxysporum, that are inoculated into tissue culture banana plantlets. At present, it is unclear at what stage in the R. similis infection process the endophytes are most effective. In this study, the effect of three endophytic F. oxysporum isolates (V5w2, Eny1.31i and Eny7.11o) on R. similis host preference of either endophyte-treated or untreated banana plants was investigated. No differences were observed between the proportion of nematodes attracted to either root segments excised from endophyte-treated or untreated plants, or in experiments using endophyte-treated and untreated tissue culture banana plantlets. These results imply that the early processes of banana plant host recognition by R. similis are not affected by endophyte infection.